How Do Nurses Percept Workplace Incivility: A Cross-Sectional Study - Ahmet Seven; Öznur Adadıoğlu; Esin Danç (Association of Nurse Managers, 2021)
Aim: This study aimed to determine how nurses perceive workplace incivility and the factors that affect their perceptions. Method: The study was performed cross-sectionally with 163 nurses who agreed to participate. The data were collected using a questionnaire containing socio-demographic features and the Nursing Incivility Scale (NIS). Data analysis was performed in a computer environment using percentage, average, and nonparametric tests. Results: The mean total score of the NIS of the nurses who participated in the study was 122.45 +- 17.33, and it was determined that the subscale means the score was 25.66 +- 5.37 (nurses in my service), 33.04 +- 7.15 (patients/visitors), 15.87 +- 4, 67 (my first manager), 22.17 +- 5.80 (doctors), and 25.69 +- 4.65 (general incivility). It was determined that there was a statistically significant difference between the variables 'education, love the profession, the place where they spent their childhood, the way they worked, and the unit' and the mean and sub-dimension mean scores of the NIS (p <0.05). Conclusion: In the study, it was seen that the nurses perceived the workplace incivility in the middle level, education, love the profession, the way of working, and the unit variables affect the level of incivility perception.